A comparison of psychological stress among women with and without reproductive failure. Issue 2 (31st October 2013) - Coughlan, Carol; Walters, Stephen; Ledger, William; Li, T.C.
Abstract: Objective: To determine whether women with recurrent implantation failure (RIF) after in vitro fertilization (IVF), similar to women with recurrent pregnancy loss, have significantly higher stress levels than women without reproductive failure, and to compare stress levels between women with RIF and women with recurrent pregnancy loss. Methods: In a questionnaire‐based study between September 2009 and January 2011, psychological stress was measured among patients attending recurrent pregnancy loss and RIF clinics at the Royal Hallamshire Hospital, Sheffield, UK. Participants completed the Fertility Problem Inventory (FPI), the Perceived Stress Scale (PSS), and the Positive and Negative Affect Schedule (PANAS) on their first visit to their respective clinic. Thirty fertile control women also completed the 3 validated questionnaires. Results: Compared with the control group, women with RIF and recurrent pregnancy loss had significantly higher scores in the FPI (RIF, P < 0.001; recurrent pregnancy loss, P = 0.003) and the PANAS negative affect domain (RIF, P = 0.004; recurrent pregnancy loss, P = 0.001), and lower scores in the PANAS positive affect domain (RIF, P < 0.001; recurrent pregnancy loss, P < 0.001). Whereas the perceived stress score (PSS) of the recurrent pregnancy loss group was significantly higher than that of the control group ( P = 0.006), the score of the RIF group was not, although the difference tended toward statistical significance ( P = 0.058). Conclusion: The study findings confirm the stressful nature of RIF and recurrent pregnancy loss.